Impact of Regulatory Incentive Programs on the Future of Pediatric Drug Development. (September 2019) - Yen, Elizabeth; Davis, Jonathan M.; Milne, Christopher-Paul
Surveys evaluating industry experience with performing pediatric studies under the Best Pharmaceutical for Children Act (BPCA) and Pediatric Research Equity Act (PREA) regulatory regime were conducted by Tufts Center for the Study of Drug Development (Tufts CSDD) in 2000, 2006, and 2016. These survey results are being used to assess the future impact of regulatory incentive programs on generating pediatric specific labeling information and development of age-appropriate drug formulations. A second perspective will be provided through the experience and expertise of neonatal/pediatric clinicians and researchers with a focus on the urgent need for the study of new and existing drugs in this vulnerable population (especially with 90% of drugs in neonates still being used off-label). This group will also address the impact of existing regulations and the likely trajectory of future pediatric drug development efforts after nearly 2 decades of regulatory incentives (both mandatory and voluntary). Finally, this review will provide input on approaches that are needed to continue to advance pediatric drug development with an emphasis on rare diseases.